Antecedents of Mobile Banking: UTAUT Model - Savić, Jovana; Pešterac, Aleksandra (The European Journal of Applied Economics, 2019)
The development of modern information and communication tech-nologies enabled banks to rely on mobile banking as an important distribution channel in their businesses. Given that investments in the development of mobile banking systems are extremely high, knowledge of which factors affect the intentions of individuals to use mobile bank-ing services can be of great importance. For this purpose, empirical research was conducted and 313 respondents were surveyed in the territory of Sumadija, Central Serbia. The collected primary data were analyzed using the statistical software SPSS v. 20. To examine the fac-tors in the work, the UTAUT model (Unified Theory of Acceptance and Use of Technology) was used. The results of empirical research indicate that all components of the UTAUT model have statistically significant influence on intention to use mobile banking, with performance ex-pectancy singled out as the most important antecedent, while effort expectancy has the weakest impact. The paper confirms the success of the UTAUT model for testing mobile banking antecedents, and gains new insights regarding the intention of using mobile banking in Serbia that can serve for managerial purposes.
Keywords: UTAUT model; intention to use mobile banking; mobile banking; modern technologies